Taxonomic And Nomenclatural Notes On Malesian Araceae I — Resolving Homalomena ovata, and a new name in Homalomena for Chamaecladon ovatum - Wong, Sin Yeng; Boyce, Peter C. (2022)
Corrections and updates are made to the taxonomy and nomenclature of Homalomena ovata Engl., Homalomena borneensis Ridl, and Chamaeclason ovatum Schott. Homalomena hostifolia Engl. is treated as a homotypic superfluous name for H. ovata Engl. Homalomena ovatum (Schott) Hook.f., an illegitimate name, is renamed Homalomena nathanielii and treated as a Singapore endemic in the Homalomena Griffithii complex.